'Adding another spinning plate to an already busy life'. Benefits and risks in patient partner–researcher relationships: a qualitative study of patient partners' experiences in a Canadian health research setting. Issue 8 (17th August 2018) - Leese, Jenny; Macdonald, Graham; Kerr, Sheila; Gulka, Lianne; Hoens, Alison M; Lum, Wendy; Tran, Bao Chau; Townsend, Anne F; Li, Linda C
Abstract : Objective: To better understand, based on patient partners' experiences, benefits and risks in patient partner–researcher relationships in a health research setting. Design: Qualitative interviews with thematic analysis informed by a relational ethics lens. Setting: A multidisciplinary health research centre in Vancouver, Canada. This study was codeveloped by patient partners and researchers at the centre. Participants: 22 people living with arthritis, with experience as members of a patient advisory board at the research centre from 1 month to 10 years. Results: We identified three main themes: (1) Being Heard: Participants had experienced uncomfortable emotions (eg, feelings of insecurity) in their relationships with researchers. The discomfort, however, was minimised by the demonstration of mutual respect in their interactions. Specifically, participants valued environments without a hierarchy between patient partners and researchers, where contributions of each party were considered equally important, and where patients' voices were heard; (2) Cobuilding social relations: Participants valued building social relations with researchers beyond their expected interactions as partners in research and (3) Adding another spinning plate to an already busy life: Participants valued relationships with researchers who had cocreated environments that minimised the risks of physical and emotional impacts (eg, fatigue, stress, guilt) on them while juggling multiple obligations, priorities and their health. Conclusions: Findings provide valuable insights to guide relationship building between patient partners and researchers. Informed by a relational ethics lens, these findings are a critical step in supporting an ethically sound practice of patient engagement in research that prioritises patients' perspectives.